THE EFFECT OF COMPUTER ANXIETY ON THE ABILITY OF ACCOUNTING STUDENTS TO USE ACCOUNTING SOFTWARE AT UNIVERSITY OF MATARAM - Puteri, Lilis Rahman; Karim, Nina Karina; Nurabiah, Nurabiah (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2024)
ABSTRACTThe purpose of this study was to empirically test and analyze the effect of computer anxiety (fear and anticipation) on the ability of accounting students to use accounting software at the University of Mataram. The type of research used in this research is associative with a quantitative approach. The study population consisted of 267 accounting students with 34 accounting students as respondents. This study conducted hypothesis testing using experimental and observation methods through practice and questionnaires with the analytical tool used, namely IBM SPSS 25. The novelty in this study is that the method used is in the form of an experimental method to measure students' abilitiy in using accounting software. The results of the study found that the variables of fear and anticipation had no effect on the ability of accounting students to use accounting software. From the experiment it was observed that students’ ability in using accounting software was more influenced by their understanding of accounting rules, not by fear and anticipation of using the computer.Keywords: Accounting Software; Anticipation; Computer Anxiety; Experiment; Fear ABSTRAKTujuan dari penelitian ini adalah untuk menguji secara empiris dan menganalisis pengaruh computer anxiety (fear dan anticipation) terhadap kemampuan mahasiswa akuntansi dalam menggunakan software akuntansi di Universitas Mataram. Jenis penelitian yang digunakan dalam penelitian ini adalah asosiatif dengan pendekatan kuantitatif. Populasi penelitian sebanyak 267 mahasiswa akuntansi dengan jumlah responden sebanyak 34 mahasiswa akuntansi. Penelitian ini melakukan pengujian hipotesis dengan metode eksperimen dan observasi melalui kuesioner dengan alat analisis yang digunakan yaitu IBM SPSS 25. Kebaruan dalam penelitian ini yaitu metode yang digunakan berupa metode eksperimen untuk mengukur kemampuan mahasiswa dalam menggunakan software akuntansi. Hasil penelitian menyatakan bahwa variabel fear dan anticipation tidak berpengaruh terhadap kemampuan mahasiswa akuntansi dalam menggunakan software akuntansi. Kesimpulan dari penelitian ini setelah dilakukan eksperimen adalah ketakutan tidak memengaruhi kemampuan dalam menggunakan software akuntansi, tetapi kemampuan software akuntansi dipengaruhi oleh pemahaman mahasiswa dalam ilmu akuntansi.Kata Kunci: Anticipation, Computer Anxiety, Eksperimen, Fear, Software Akuntansi